RC Hovercraft: An I-Bylogical Enzyme (I-BE) Biosensor Carrier - Rinta Kridalukmana; Budi Cahyo S.P.; Deddy Kurniawan W; Fahmi Arifan (Institute of Advanced Engineering and Science, 2017)
In this research, a hovercraft was developed as a transportation tool to carry an I-Bylogical Enzyme (I-BE) biosensor. The main function of the biosensor is to measure the level of dangerous chemical materials from factory’s liquid waste. Hence, fiber and acrylic materials, that widely known for its resistance to chemical reaction, are needed to build the hovercraft. By using Atmega 8535 microcontroller and Arduino Uno board, a remote control was choosen to navigate hovercraft’s movement with support of 6 channels Transmitter Receiver. As a result, after series of tests that were carried out, indicate that the hovercraft’s prototype was found to meet design and requirements expectation.